Esthetic multidisciplinary rehabilitation of patient with central incisor agenesis - Mascarenhas, Vinicius I. [UNESP]; Leandrin, Thaís P. [UNESP]; Lorenzetti, Camila C. [UNESP]; De Castro, Camila L. [UNESP]; Saad, Jose R. C. [UNESP] (Jaypee Brothers Medical Publishing, 2018)
Aim: The aim of this case report was to restore the esthetic smile of a patient with agenesis of maxillary right central incisor, while discussing the most important topics in a multidisciplinary approach. Background: Due to the absence or loss of some teeth in the anterior region, it becomes a challenge in oral rehabilitation. Restoration of function and esthetics may require a multidisciplinary treatment that can start with periodontal, orthodontic, surgical, implantology, or restorative evaluation. Case report: A 28-year-old patient with agenesis of the maxillary right central incisor was looking to improve the esthetics of his smile. The patient had right superior lateral incisor positioned in place of the central and the canine in the position corresponding to the lateral incisor, which compromised the dental and gingival esthetics. After analyses and digital smile design (DSD), surgeries for gingival smile correction, gingivectomy (teeth 12, 14, and 15), and gingival tissue grafts (tooth 13) were made. After a period of 2 months, preparations were made on teeth 12, 13, and 14 for ceramic laminates following the initial DSD. After 1 year of cementation, maintenance and stability of gingival margin, as well as the integrity of laminate ceramic were observed. Conclusion: In conclusion, a correct prior planning of esthetic rehabilitation is the best way to achieve excellent results to meet the needs and objectives of each patient. Often, a multidisciplinary treatment involving surgical and restorative procedures should be taken into consideration, with the appropriate choice of techniques and materials to be used. Clinical significance: The treatment performed on the patient allowed the esthetic improvement of gingival architecture and installation of ceramic restorations with function and esthetics similar to natural teeth.
Keywords: Connective tissue; Dental agenesis; Esthetics